Genomic data from Northern rockhopper penguin ( Eudyptes moseleyi ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Northern rockhopper penguin (also known as Moseley's rockhopper penguin or Moseley's penguin) is a small crested penguin closely related to the Eastern and Western rockhopper penguins. The Northern rockhopper penguin breeds on Amsterdam and Gough islands. They breed in colonies at sea level, on cliff sides and sometimes inland. Populations of the Northern rockhopper penguin have declined drastically, and the International Union for Conservation of Nature (IUCN) classifies them as endangered. We sequenced the genome of an adult Northern rockhopper penguin from Amsterdam Island, Southern Indian Ocean (provided by Yves Cherel) to a depth of approximately 139x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.23Gb, with the contig and scaffold N50 values of 20.86Kb and 2.14Mb respectively. We identified 16812 protein-coding genes. ...